PENGARUH TEKNOLOGI INFORMASI TERHADAP PERKEMBANGAN UMKM DI KECAMATAN LUBUK KILANGAN KOTA PADANG - Rasyidah Zahidah; Novera Martilova (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The purpose of this study was to see the effect of information technology on the development of MSMEs in Lubuk Kilangan District, Padang City. This research is a quantitative descriptive research using a questionnaire (Likert scale). The number of samples is 95 respondents. And with the method of data analysis used to test the validity, reliability, classical assumptions (normality test, autocorrelation test), simple linear regression test, test the coefficient of determination R², and test the hypothesis (t test). The results of this study indicate that the regression coefficient has a value of 0.616. If it increases for every 1 unit of information technology variable, it will affect the development of MSMEs by 0.616. Then the calculated t value is 8.537 and the t table is 1.986 which is calculated > t table (8.537 > 1.986), then the sig is obtained at 0.000 <0.05. From this it can be seen that the information technology variable (X) has an influence on the MSME development variable (Y). then the results of the R² (R Square) test obtained a value of 0.439 or 43.9% which can be interpreted that the independent variable (information technology) has an influence of 43.9% on the dependent variable (business development) and the remaining 56.1% is influenced by other factors such as the ease of borrowing business capital and government policies. Based on the information technology t test, it partially has a significant effect on the development of MSMEs in Lubuk Kilangan District, Padang City.